2017
DOI: 10.1074/jbc.m116.748103
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-36 Modulates Blood Glucose and Body Weight Independently of Canonical APJ Receptor Signaling

Abstract: Edited by Jeffrey E. PessinApelin-36 was discovered as the endogenous ligand for the previously orphan receptor APJ. Apelin-36 has been linked to two major types of biological activities: cardiovascular (stimulation of cardiac contractility and suppression of blood pressure) and metabolic (improving glucose homeostasis and lowering body weight). It has been assumed that both of these activities are modulated through APJ. Here, we demonstrate that the metabolic activity of apelin-36 can be separated from canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…As anticipated, we observed the beneficial effects of Fc‐apelin‐13 treatment in obese mice by improving glucose disposal. Interestingly, Fc‐apelin‐13 did not affect body weight, which is consistent with a recent report that AAV‐mediated apelin‐36 over‐expression does not modulate body weight gain in mice being fed with high fat diet . Obese mice fed with high‐fat‐diet develop steatosis and mild fibrosis in the liver .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As anticipated, we observed the beneficial effects of Fc‐apelin‐13 treatment in obese mice by improving glucose disposal. Interestingly, Fc‐apelin‐13 did not affect body weight, which is consistent with a recent report that AAV‐mediated apelin‐36 over‐expression does not modulate body weight gain in mice being fed with high fat diet . Obese mice fed with high‐fat‐diet develop steatosis and mild fibrosis in the liver .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Fc-apelin-13 did not affect body weight, which is consistent with a recent report that AAV-mediated apelin-36 over-expression does not modulate body weight gain in mice being fed with high fat diet. 42 Obese mice fed with high-fat-diet develop steatosis and mild fibrosis in the liver. [43][44][45] We have found that the Fc-apelin-13 treatment ameliorates hepatic steatosis by reducing triglyceride content and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…reported in metabolic diseases where it decreased adiposity, serum insulin and increased insulin sensitivity 16,17 ; and in renal diseases where it decreased acute renal injury and fibrosis 18 . It has recently emerged that apelin has pro-tumorigenic effects in various cancer models possibly by promoting angiogenesis and that inhibition of the apelin pathway was protective against tumour growth 14,19 .…”
mentioning
confidence: 99%
“…A clinical trial on the influence of pyr1‐apelin‐13 (exopeptidase degradation resistant) on insulin sensitivity in healthy overweight men has been completed and shown to significantly improve insulin sensitivity in a hyperinsulinemic–euglycemic clamp study as well as cause no adverse effects due to apelin administration . A long circulating PEGylated variant of apelin‐36 was found to significantly lower blood glucose and improve glucose tolerance in diet‐induced obese mice …”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 99%